Continuous Real‐Time Detection of H2, He, and 222Rn While Drilling DIVE‐1 Boreholes (ICDP) Indicates Deep Fracture Fluid Migration in Crystalline Rocks - H. Dutoit; L. Truche; F. V. Donzé; T. Wiersberg; M. L. Doan; J. Li; A. Greenwood; E. Caspari; N. Lefeuvre; J. Dominique; S. Auclair; L. Masci; et al. (Geochemistry, Geophysics, Geosystems)
Abstract The identification and real‐time monitoring of geofluids during drilling is crucial for safe drilling operations and can provide valuable insights into reservoir properties and fluid migration. While mud gas logging is well established in oil and gas exploration, recent interest in natural hydrogen (H2) and helium (He) exploration has prompted the need for improved mud gas logging techniques for continuous wireline coring in crystalline bedrock. The detection of both H2 and He is particularly useful when exploring these two commodities but also for identifying deep fluid migration notably in crystalline bedrock. This study presents the results of mud gas logging of O2, N2, 40Ar, 38Ar, 36Ar, CO2, CH4, H2, He, and 222Rn from two boreholes (909.5 and 578.5 m deep) drilled in the Ivrea‐Verbano Zone (Northern Italy) as part of the DIVE‐ICDP project. Comparison with data from geophysical logging showed that gas peaks correlate well with variations in the physical characteristics of the well fluid, indicating zones of fluid inflow. Real‐time gas monitoring proved to be valuable for identifying deep gas migration and aiding decision‐making. Despite its potential, this technique faces challenges, such as distinguishing between formation‐derived and drilling‐induced gases. Complementary analyses, including isotopic studies, are recommended to refine source identification. Nevertheless, the correlation of He and H2 with CH4 and CO2 provides initial insights into their possible origins, making this method a promising tool for exploring H2 and He gases in deep geological formations.